Self-supported amorphous nickel-iron phosphorusoxides hollow spheres on Ni-Fe foam for highly efficient overall water splitting. (1st October 2021) - Song, Shiwei; Zang, Jianbing; Zhou, Shuyu; Gao, Hongwei; Tian, Xueqing; Yuan, Yungang; Li, Wei; Wang, Yanhui
Highlights: The binary NFF substrate was selected as source of Fe and Ni elements. The NiFe-POx /NFF was prepared by in-situ oxidation of NFF and phosphorylation. Hollow nanospheres were synthesized with the assistance of oxygen bubble templates. The fluffy featherlike amorphous NiFe-POx nanoflakes possessed abundant active sites. The bifunctional electrocatalysts of NiFe-POx /NFF achieved overall water splitting. Abstract: The development of high-efficiency and economical bifunctional electrocatalysts in hydrogen evolution reactions (HER) and oxygen evolution reactions (OER) plays a key role in overall water splitting. In this study, a success was achieved in synthesizing the hollow nanospheres with amorphous nickel-iron phosphorusoxides nanoflakes layer grown on Ni-Fe foam (NiFe-POx /NFF). Firstly, with the assistance of oxygen bubbles templates, the hollow spheres comprised of NiFe-OH nanosheets were produced through the in-situ chemical oxidation of NFF surface. After phosphorylation, crystalline NiFe-OH nanosheets were transformed into amorphous NiFe-POx with plenty of defects and disorders, thus improving the density of active sites. The catalytic performance of NiFe-POx /NFF was further improved by a combination of stable 3D hierarchical nanostructure, effective mass transport and charge transfer, as well as the electrochemical specific surface area expanded by fluffy featherlike nanoflakes. The self-supported electrode of NiFe-POx /NFF exhibited outstanding catalytic property in the presence of alkaline electrolyte, including a small overpotential of 110 and 247 mV required to achieve 50 mA cm −2 for HER and OER in 1.0 M KOH aqueous solution, respectively. As a bifunctional electrocatalyst, NiFe-POx /NFF could provide a low cell voltage of 1.52 V to reach 20 mV cm −2 under a two-electrode system as required for the occurrence of overall water electrolysis under alkaline medium, while showing extended durability under continuous electrolysis without degradation. Graphical abstract: Image, graphical abstract